441 Late-Breaking: Exosomal activity in maternal circulation of ewes exposed to ergot alkaloids during mid – late gestation. (7th December 2018) - Duckett, S; Britt, J; Zhou, Z; Miller, M
Abstract: Plasma exosome concentrations increase as pregnancy advances in humans, but little is known about the exosomal activity in ovines. The objective of this study was to assess the influence of ergot alkaloid exposure on exosomal bioactivity in maternal circulation. Thirty-six Suffolk ewes (78.24kg) estimated to be carrying twins at d35 of gestation were randomly assigned to one of two dietary treatments: endophyte-free tall fescue seed (E-; 0.0μg ergovaline + ergovalinine/g) or endophyte-infected tall fescue seed (E+; 4.14μg ergovaline + ergovalinine/g) at one of two stages of gestation: MID (d35–85) or LATE (d86 –133) creating four treatments. Endophyte-infected tall fescue seed was fed to provide 1772μg of ergovaline + ergovalinine/hd/d for E+ treatments while an equal weight of endophyte-free seed was fed for E- treatments. Maternal blood samples were collected at d29, 50, 85, 105, and 133. Fetal and maternal terminal surgeries were performed at d133 of gestation, and placental and fetal weights were collected. A subsample (n=4) of E+/E+ and E-/E- treatments were selected for exosome isolation with the ExoQuick Plasma Prep kit. Acetylcholinesterase is an exosome specific enzyme used to identify and measure exosomal activity through colorimetric assays. Acetylthiocholine (1.25mM) and 5, 5'-Dithiobis 2-nitrobenzoic acid (0.1mM) were added to the exosomal fraction and kinetic absorbance was read at 412nm for 30min at 37°C at 5-minute intervals. Data were analyzed using a mixed procedure in SAS 9.3 with significance set at P < 0.05. There was no correlation between exosomal activity and fetal or placental weight. Exosomal activity tended (P =0.098) to be higher for E+/E+ ewes at d105 of gestation compared to E-/E- ewes. Gestation day influenced (P =0.0298) exosomal activity with ewes at d133 exhibiting reduced (P=0.036) activity compared to d85. In ovine pregnancies, exosomal activity remained stable through MID gestation but declined at d133.